Psychologiczne konsekwencje poczucia zagrożenia doświadczanego w sytuacji pracy - Mamcarz, Piotr; Mamcarz, Izabela; Suchocka, Lilia (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
This article is an attempt of presenting feeling of threat problem as well as connecting this phenomenon with psychological components of persons functioning in dangerous work environment conditions. Subject of feeling of threat can be understood as “experiencing apprehension concerning results of potential/actual dangers”, oscillates in terminological area of anxiety, fear, stress, restlessness and it highlights a cognitive process distinctive for listed phenomenon’s. Together with technological and organization changes increases number of health problems affecting workers in different institutions. The hardest work conditions affect people working in high-risk occupation. Physical factors of work environment as well as coexisting psychic occurrence affects multidimensional functioning of worker not only in terms of working conditions. The analysis of feeling of threat and its correlates is going to be presented based on empirical study executed on group of 304 (100 firefighters, 100 miners, and 104 employees of chemical factory). Obtained results will be used to present dependence between multidimensional functioning of person in dangerous work environment and feeling of threat.